Pengembangan Media Pembelajaran Multimedia Interaktif CAI Pada Mata Pelajaran Mekanika Teknik Kelas X Di SMK Negeri 1 Jakarta - Ellis Yuniar Hanida; Tuti Iriani; Riyan Arthur (Jurnal Pensil : Pendidikan Teknik Sipil, 2015)
The objectives of this research was designed to : (1) Develop interactive multimedia learning of class X of engineering mechanics on the simple beam construction subjects. (2) Determine the feasibility of the developed media learning. (3) Knowing whether the resulting product can improve learning outcomes in a simple beam construction subjects.This research is a R&D (Research and Development). The method used is an experimental method. Validated by expert instructional media content and media experts to get the feasibility trial. Further trials conducted on students of class X of expertise Building Engineering at SMK Negeri 1 Jakarta totaling 83 people. Analysis results of students learning used t-test independent samples of the two parties with software SPSS 22.The results of this development means that the experimental class obtain the mean difference in learning outcomes (pre -test and post-test ) of 38.46 and a spike of 19.21 % . While the control class, obtained a mean difference of learning outcomes (pre -test and post-test ) of 26.59 and a spike of 13.3% . So we can conclude interactive multimedia learning development more effectively used in the learning process of engineering mechanics in class X SMK Negeri 1 Jakarta